2019
DOI: 10.1007/s00018-019-03249-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-peptidyl small molecule, adenosine, 5′-Se-methyl-5′-seleno-, 2′,3′-diacetate, activates insulin receptor and attenuates hyperglycemia in type 2 diabetic Leprdb/db mice

Abstract: The pathophysiology of type 2 diabetes mellitus (T2D) is characterized by reduced or absent insulin receptor (INSR) responsiveness to its ligand, elevated hepatic glucose output and impaired glucose uptake in peripheral tissues, particularly skeletal muscle. Treatments to reduce hyperglycemia and reestablish normal insulin signaling are much sought after. Any agent which could be orally administered to restore INSR function, in an insulin-independent manner, would have major implications for the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 39 publications
8
36
0
Order By: Relevance
“…However, it should also be pointed out that we previously have demonstrated that NPC43 inhibits hepatic gluconeogenesis in T2D mice, through Insr/Akt activation and G6pc suppression. 8 In the present study, we again observed NPC43driven Insr/Akt activation in the liver (figures 4-5) and so would surmise that suppressed gluconeogenesis may contribute to reducing blood glucose in T1D also.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…However, it should also be pointed out that we previously have demonstrated that NPC43 inhibits hepatic gluconeogenesis in T2D mice, through Insr/Akt activation and G6pc suppression. 8 In the present study, we again observed NPC43driven Insr/Akt activation in the liver (figures 4-5) and so would surmise that suppressed gluconeogenesis may contribute to reducing blood glucose in T1D also.…”
Section: Resultssupporting
confidence: 75%
“…9 In brief, STZ (Cat #S0130, Sigma-Aldrich, St Louis, Missouri) was dissolved in 0.05 M sodium citrate buffer and intraperitoneally injected into male C57BL/6J mice (4-5 weeks old) at a dose of 55 mg/ kg body weight (mpk) daily for 5 days. After STZ injection, these mice were housed in the pathogenfree vivarium for 14-48 days and blood glucose levels were measured using a glucometer as described in Lan et al 8 Serum insulin levels in these mice at 48 days post-intraperitoneal STZ treatment were also determined using Thermo Fisher Scientific's Mouse Insulin ELISA-Kit (Cat #EMINS), according to the manufacturer's protocol.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations